Perancangan Sistem Informasi Pergudangan dengan Metode Framework for The Application System Thinking (Fast) Berbasis VBA Macro Excel (Studi Kasus PT. Meidoh Indonesia) - Fauzi Alfi Yasin; Rianita Puspa Sari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
The development of information technology is growing very rapidly, as evidenced by the birth of Industry 4.0. Industry 4.0 has entered all aspects of life, the manufacturing industry and the service industry. One of the purposes of the use of information technology is to increase the effectiveness and efficiency of a process and the company's competitive advantage. PT. Meidoh Indonesia, which is located in Karawang, has begun to apply Industry 4.0 technology, especially in the field of improving material flow. The process of taking employee work equipment is still conventionally using the material request paper. This study aims to design an employee work equipment warehousing information system using the Framework For The Application System Thinking (FAST) method based on VBA Macro Excel. The results showed that this information system makes it easier for employees to make requests for work equipment to support their work. Information systems can reduce times of request material up to 60%. The fastest material request time conventionally takes 15 minutes, while material request time using this warehousing information system only takes 5 minutes.